Outcome following repair of a tibial nerve transection resulting from total ankle arthroplasty: A case report - Michelle K. Yoakim, DPM; Gregory P. Still, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases, 2024)
Tibial nerve injury is a rare complication of total ankle arthroplasty (TAA) that has been outlined in the literature. However, the literature is sparse regarding the treatment of iatrogenic tibial nerve injury in situations of delayed diagnosis. This case report highlights a nerve repair technique using a nerve graft for a severe complication associated with total ankle arthroplasty. Our patient had a TAA in November 2021, and presented to our clinic in March 2022 with loss of sensation and increasingly rapid loss of the motor function in the tibial nerve distribution. Nerve conduction and electromyography studies revealed injury to the deep peroneal and tibial nerves at the lower leg. Surgical intervention revealed a large neuroma-in-continuity with near complete transection of the tibial nerve. She subsequently underwent large neuroma excision, and tibial nerve repair with nerve graft. This procedure resulted in almost complete reversal of symptoms including pain relief and improvement in motor function. While tibial nerve injury during TAA is rarely reported, it is likely unrecognized or misdiagnosed resulting in significant complication for patients. Where complete or near-complete nerve transection results in neuroma formation, we recommend repair using a nerve graft as neuroma resection with end-to-end repair has been shown to have high failure rates with recurrence in the foot. Nerve grafts reduce the risk of recurrent symptomatic neuromas by allowing nerve endings to exhaust any subsequent outgrowth.